Choices which change life satisfaction: Revising SWB theory to account for change - Bruce Headey; Ruud Muffels; Gert G. Wagner (Institute for the Study of Labor (IZA), 2010)
Using data from the long-running German Socio-Economic Panel (SOEP) 1984-2008, this paper analyses the effects of individual preferences and choices on subjective well-being (SWB). It is shown that preferences and choices relating to life goals/values, partner's personality, hours of work, social participation and healthy lifestyle all have substantial effects on life satisfaction. The results have negative implications for the still dominant theory of SWB, set-point theory. This theory holds that adult SWB does not change in the medium or long term, although temporary fluctuations occur due to specific life events. Set-point theory has come under increasing criticism in recent years, primarily due to unmistakable evidence in SOEP that, during the last 25 years, up to a third of the population has recorded substantial and apparently permanent changes in life satisfaction. It is becoming clear that the main challenge now for SWB researchers is to develop a new theory which can account for medium and long term change, and not merely stability in SWB. Set-point theory is limited precisely because it is purely a theory of stability. The paper is based on a specially constructed SOEP file in which data are divided into five 5-year periods in order to facilitate analysis of medium term change.
Keywords: I31; J1; Z13; 330; SWB; set-point theory; life goals; individual choice; panel regression analysis; SOEP; Lebenszufriedenheit; Lebensqualität; Entscheidung; Präferenztheorie; Theorie; Deutschland